Translation and Initial Validation of the Chinese (Cantonese) Version of Cognitive Flexibility Inventory Using People with Mental Illness - Sui Lung Wong; Tai Wa Liu; Chi Chiu Lee; Pui Wong (Mental Illness)
Introduction. The Cognitive Flexibility Inventory (CFI) is a self-administered instrument comprising 20 items on a 7-point Likert scale, designed to measure an individual’s level of cognitive flexibility (CF). Low CF levels have been associated with mental health issues including impulsive personality traits, anxiety, depression, and suicidal ideation. Assessing CF can help mental health professionals with evaluating the outcomes of psychological interventions and conducting comprehensive assessments. However, there is a scarcity of tools specifically designed for Cantonese-speaking individuals. This study examined the psychometric properties of a Cantonese version of the CFI (CFI-CAN) using a sample of Cantonese-speaking psychiatric outpatients receiving community psychiatric services. Method. The CFI-CAN was developed using the standard translation-back-translation process. The study recruited a sample of 104 participants from a group of Cantonese-speaking psychiatric outpatients receiving psychiatric service in Hong Kong. All of them were aged 18 years or older, with a mean age of 39.43 (SD=11.04), and 75.96% was employed either full time or part time. The psychometric validation of the CFI-CAN included assessing content validity through item and scale level, internal consistency using Cronbach’s alpha, test-retest reliability through the intraclass correlation coefficient, minimal detectable change (MDC) using the MDC95 equation, examining floor and ceiling effects, and establishing convergent validity through the Spearman correlation coefficient. Results. Content validity was excellent (I-CVI and S-CVI/UA=1). Internal consistency was excellent (Cronbach’s alpha=0.91, mean=64.07, SD=12.36). Test-retest reliability over 4 weeks was excellent (ICC3,1=0.905, 95% CI=0.839-0.945). MDC was calculated as 14.94. No observed floor and ceiling effect. Convergent validity was established with negative correlation with Chinese version of Perceived Stress Scale (r=−0.610, p<0.001). Conclusions. The CFI-CAN is the first validated instrument for measuring cognitive flexibility specifically in Cantonese-speaking psychiatric outpatients. Its psychometric properties are comparable to the original version. Implementing the CFI-CAN can benefit mental health professionals in assessing cognitive flexibility and understanding changes in cognitive flexibility for cognitive-based interventions in Cantonese-speaking psychiatric outpatients.